Management of Oro-Antral Communication: A Systemic Review of Diagnostic and Therapeutic Strategies - Gianna Dipalma; Angelo Michele Inchingolo; Irma Trilli; Laura Ferrante; Angela Di Noia; Elisabetta de Ruvo; Francesco Inchingolo; Antonio Mancini; Stefan Cocis; Andrea Palermo; Alessio Danilo Inchingolo (Diagnostics)
Aim: This study aims to evaluate the management of oro-antral communications (OAC) and fistulas (OAF), focusing on treatment strategies based on defect size, epithelialization, and the presence of sinus infections, while exploring both traditional and emerging techniques. Materials and Methods: The systematic review was conducted following the PRISMA guidelines and registered on PROSPERO (CDR ID 623251). Using targeted keywords, articles in English published within the last 10 years were analyzed from databases such as PubMed, WoS and Scopus, selecting only clinical studies on human patients. After thorough screening, 20 publications were included in the qualitative analysis, among 734 initially identified. Results: Small OACs (<5 mm) were managed conservatively with hemostatic materials, while larger defects (>5 mm) required surgical closure, with the Bichat flap proving highly effective for large defects. Innovative treatments using autologous bone grafts and PRF showed promise in supporting tissue regeneration. In cases with sinusitis, the combination of FESS and intra-oral closure techniques resulted in high success rates for infection resolution and defect closure. Conclusions: Treatment outcomes for OAC and OAF are highly dependent on the size of the defect and the presence of sinusitis. Multidisciplinary collaboration, along with timely surgical intervention and adherence to medical therapies, is essential for successful management. Emerging techniques and minimally invasive procedures continue to improve patient outcomes, offering hope for more effective and sustainable solutions in complex cases.